ACHIEVEMENTS AND SHORTCOMINGS OF MARK REESE AND KAROL ERMAKOVA’S TRANSLATIONS OF ABDULLA QADIRI’S NOVEL "BYGONE DAYS" - Ergasheva , Mushtariy (Educational Research in Universal Sciences, 2024)
This article is devoted to the translations of Abdulla Qadiri’s novel “Bygone Days” by Mark Reese and Karol Ermakova, highlighting both the achievements and shortcomings of their respective translations. The authors discuss how each translator brings unique strengths to the table, while also acknowledging areas where their work may have fallen short. This analysis sheds light on the complexities of translation and the nuances involved in conveying the original work’s meaning and style in a new language.